2007
DOI: 10.1002/ange.200702160
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung Nickel‐katalysierter Oxidationen von Alkenen: eine Diaminierung durch Sulfamid‐Transfer

Abstract: Nickel kann auch oxidieren! Nickel(II)‐Salze wie Nickelchlorid und Nickelacetylacetonat katalysieren die intramolekulare Diaminierung von Alkenen mit Harnstoff‐ und Guanidinderivaten sowie Sulfamiden als Stickstoffquellen. Besonders letztere bieten sich als Substrate an, da mit ihnen eine selektive und einfache Freisetzung der Diamine aus den Oxidationsprodukten gelingt (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Recent progress has demonstrated the ability of several transition metals to catalyze this transformation, including palladium,3,4 copper,5 nickel6 and gold 7. These reactions share a common concept of intramolecular aminometalation as the initial step and hence give rise to concomitant formation of heterocycles such as pyrrolidines 8…”
Section: Methodsmentioning
confidence: 99%
“…Recent progress has demonstrated the ability of several transition metals to catalyze this transformation, including palladium,3,4 copper,5 nickel6 and gold 7. These reactions share a common concept of intramolecular aminometalation as the initial step and hence give rise to concomitant formation of heterocycles such as pyrrolidines 8…”
Section: Methodsmentioning
confidence: 99%
“…Intramolecular olefin diaminations form nitrogen heterocycles directly and has predominantly been accomplished by using tethered amine nucleophiles wherein both amine additions occur in an intramolecular fashion (Scheme ). This olefin diamination strategy has been successfully employed by using palladium,4a nickel,4b and gold4c catalysts, and stoichiometric copper reagents,3 and has resulted in the synthesis of a number of interesting compounds, such as bicyclic sulfamides, ureas, and guanidines. An intra/intermolecular alkene diamination procedure would result in the convergent formation of one new nitrogen heterocycle along with the installation of a differently functionalized amine substituent.…”
Section: Methodsmentioning
confidence: 99%
“…[1] As a result, significant progress has been made recently in this aspect with the development of new transition metalcatalyzed proc 2] When the olefin diamination is realized in an intramolecular manner by tethering one (or two) nitrogen atom(s) with the alkene moiety, functionalized nitrogen heterocycles will be furnished. As such, several important methodologies employing palladium, [3] nickel, [4] gold, [5] and copper [6] as catalyst have been developed for this purpose. However, these studies mainly deal with unsaturated amide or sulfonamide derivatives, whereas reactions involving other types of nitrogen sources have much less been explored.…”
Section: Abstract: Azidation; Copper Catalysis; Cyclization; Dihydropmentioning
confidence: 99%
“…To achieve this goal, we initiated the study by choosing TMSN 3 and NaN 3 as the azidation agents, and several low-valent copper species such as CuBr·SMe 2 , Cu(CH 3 CN) 4 PF 6 (shorten as CuPF 6 below), Cu powder and Cu 2 O as catalyst to promote the reaction of (E)-1-phenylpent-4-en-1-one O-benzoyl oxime (1a). [14] Preliminary results showed that when TMSN 3 was used as the azide source, the desired reaction could happen, but NaN 3 was invalid under the same conditions.…”
Section: Abstract: Azidation; Copper Catalysis; Cyclization; Dihydropmentioning
confidence: 99%
See 1 more Smart Citation